2014
DOI: 10.3389/fnana.2014.00063
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy, histochemistry, and immunohistochemistry of the olfactory subsystems in mice

Abstract: The four regions of the murine nasal cavity featuring olfactory neurons were studied anatomically and by labeling with lectins and relevant antibodies with a view to establishing criteria for the identification of olfactory subsystems that are readily applicable to other mammals. In the main olfactory epithelium and the septal organ the olfactory sensory neurons (OSNs) are embedded in quasi-stratified columnar epithelium; vomeronasal OSNs are embedded in epithelium lining the medial interior wall of the vomero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
91
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 65 publications
(77 reference statements)
4
91
2
1
Order By: Relevance
“…Salazar and Sánchez Quinteiro [2003] as well as Barrios et al [2014] have also reported that UEA-I reacts with receptor cells of the VNE that express vomeronasal receptor 1 in the middle region, but not with those that express vomeronasal receptor 2 in the basal region. Because the rostral and caudal glomeruli of the mouse receive input fibers from vomeronasal receptor cells expressing vomeronasal receptors 1 and 2, respectively, UEA-I has generally been regarded as an indicator of glomeruli that possess different properties.…”
Section: Uea-i Reaction In the Aobmentioning
confidence: 99%
See 4 more Smart Citations
“…Salazar and Sánchez Quinteiro [2003] as well as Barrios et al [2014] have also reported that UEA-I reacts with receptor cells of the VNE that express vomeronasal receptor 1 in the middle region, but not with those that express vomeronasal receptor 2 in the basal region. Because the rostral and caudal glomeruli of the mouse receive input fibers from vomeronasal receptor cells expressing vomeronasal receptors 1 and 2, respectively, UEA-I has generally been regarded as an indicator of glomeruli that possess different properties.…”
Section: Uea-i Reaction In the Aobmentioning
confidence: 99%
“…Some studies [Lipscomb et al, 2003;Salazar and Sán-chez Quinteiro, 2003;Barrios et al, 2014] have found that UEA-I reacts more intensely with rostral than caudal glomeruli in the AOB. Salazar and Sánchez Quinteiro [2003] as well as Barrios et al [2014] have also reported that UEA-I reacts with receptor cells of the VNE that express vomeronasal receptor 1 in the middle region, but not with those that express vomeronasal receptor 2 in the basal region.…”
Section: Uea-i Reaction In the Aobmentioning
confidence: 99%
See 3 more Smart Citations